The Six Sigma project planner : a step-by-step guide to leading a Six Sigma project through DMAIC - Pyzdek, Thomas (McGraw-Hill, 2003)
'The Six Sigma Project Planner' is designed to be used by the leaders of a Six Sigma initiative, to plan and implement prioritized Six Sigma projects.